Effectiveness of Body Positioning in Improving Oxygen Saturation in Pediatric Patients with Bronchopneumonia: A Systematic Review Based on Kolcaba’s Comfort Theory - Shalsa Nurmajidah Malik; Nopi Nur Khasanah; Herry Susanto; Sri Wahyuni (GLOBAL HEALTH SCIENCE GROUP, 2026)
Bronchopneumonia is a lower respiratory tract infection that frequently leads to impaired gas exchange and hypoxemia in children. Non-pharmacological interventions, such as body positioning, play a crucial role in nursing management. Kolcaba’s Comfort Theory offers a holistic approach by addressing physical, psychospiritual, environmental, and social dimensions to enhance patient comfort. This systematic review aims to evaluate the effectiveness of various body positions in improving oxygen saturation among pediatric patients with bronchopneumonia through the lens of Kolcaba’s Comfort Theory. This systematic review followed the PRISMA guidelines and utilized PubMed and Google Scholar databases to identify relevant studies published between 2020 and 2024. The search was guided by the PICO framework with keywords including body positioning, semi-Fowler position, oxygen saturation, bronchopneumonia, pediatric patients, and Kolcaba’s Comfort Theory. From 400 initially retrieved articles, 120 duplicates were removed, leaving 280 for screening. Titles and abstracts were reviewed for relevance, and 25 full-text articles were assessed for eligibility based on inclusion criteria. After applying these criteria, 10 studies were included for detailed analysis. Each selected study was then critically appraised using the Joanna Briggs Institute (JBI) Critical Appraisal Tools to assess methodological quality, data validity, and alignment with Kolcaba’s Comfort Theory. Analysis of the 10 included studies demonstrated that body positioning interventions (such as semi-Fowler’s, right lateral, and semi-recumbent positions) were significantly effective in increasing oxygen saturation (SpO₂) in children with bronchopneumonia. Based on Kolcaba’s theory, body positioning not only enhances physical comfort by optimizing ventilation but also reduces anxiety (psychospiritual dimension) and improves environmental comfort. Body positioning is an effective nursing intervention for improving oxygen saturation in pediatric patients with bronchopneumonia. The application of Kolcaba’s Comfort Theory underscores that the effectiveness of this intervention is mediated through the multidimensional enhancement of patient comfort.